Multicenter, prospective cohort study of oesophageal injuries and related clinical outcomes (MUSOIC study) - Owen, RP; Chidambaram, S; Griffiths, EA; Sultan, J; Phillips, AW; Vohra, R; Preston, S; Gossage, J; Hanna, GB; Underwood, TJ; Maynard, N; Markar, SR (Lippincott, Williams & Wilkins, 2023)
Objective: To identify prognostic factors associated with 90-day mortality in patients with oesophageal perforation (OP), and characterize the specific timeline from presentation to intervention, and its relation to mortality.